2020
DOI: 10.1080/14737167.2020.1807943
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden on health care by pain severity and usual analgesic treatment in patients with symptomatic osteoarthritis: a Spanish nationwide health survey

Abstract: Objectives: To estimate disease burden on healthcare in osteoarthritis (OA) pain patients in Spain, and to determine whether frequency of healthcare resource utilisation (HRU) and related costs differ by pain severity and treatment with usual analgesics. Methods:The 2017 Spanish National Health Survey (ENSE), a large, nationwide, cross-sectional general health survey, was used to abstract data on adult patients with a self-reported physician diagnosis of OA. Patients were cross-classified according to pain sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Previously, studies have reported significantly higher healthcare expenditures in adults with osteoarthritis compared to those without osteoarthritis 43 , 44 and higher expenditures due to pain. 19 , 20 In this study, we restricted our analysis to adults with osteoarthritis and examined excess healthcare expenditures associated with pain interference. We found that adults with osteoarthritis and pain had 2.01 times higher annual healthcare expenditures compared to those without pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, studies have reported significantly higher healthcare expenditures in adults with osteoarthritis compared to those without osteoarthritis 43 , 44 and higher expenditures due to pain. 19 , 20 In this study, we restricted our analysis to adults with osteoarthritis and examined excess healthcare expenditures associated with pain interference. We found that adults with osteoarthritis and pain had 2.01 times higher annual healthcare expenditures compared to those without pain.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that healthcare expenditures were higher in adults with osteoarthritis and severe pain compared to those with moderate or no pain. 19 , 20 The presence of comorbidities may affect pain severity and contribute to the disease burden including higher healthcare expenditures among adults with osteoarthritis. 5 , 21 Thus, it is important to understand the factors that drive excess expenditures associated with pain among adults with osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…OA is the most prevalent joint disorder and source of chronic pain and disability in developed countries [ 5 , 6 ]. This degenerative disease of the joint affects the locomotor system and is characterised by a loss of articular cartilage, as well as an osseocartilaginous proliferation of the subchondral and articular margins [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…23 Likewise, OA exerts a significant impact on healthcare systems, given the substantial costs associated with joint replacement surgery, specialist consultation and the use of prescription medicines, amongst other resources, to manage moderate to severe pain. [19][20][21]24 In Spain, OA healthcare costs were on average €2274 per patient per year; projecting the actual prevalence of OA, 15 the actual national costs would be €11.2bn, or 0.96% of the 2017 Spanish gross domestic product. 24 On the other hand, there was a worldwide doubling in the use of opioids for pain relief between the years 2010 and 2019, with high levels of opioid use evident in developed Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21]24 In Spain, OA healthcare costs were on average €2274 per patient per year; projecting the actual prevalence of OA, 15 the actual national costs would be €11.2bn, or 0.96% of the 2017 Spanish gross domestic product. 24 On the other hand, there was a worldwide doubling in the use of opioids for pain relief between the years 2010 and 2019, with high levels of opioid use evident in developed Western countries. [25][26][27][28] Opioids have the potential to cause harm, both short-and long-term, in all subjects 727,356 chronic OA pain patients per day; 41.8% on strong opioids.…”
Section: Introductionmentioning
confidence: 99%